Influence of non-thermal argon plasma needle on blood coagulation - Aadim, Kadhim A. (Iraqi Journal of Physics, 2019)
Non-thermal argon plasma needle at atmospheric pressure wasconstructed. The experimental setup was based on a simple and lowcost electric component that generates a sufficiently high electricfield at the electrodes to ionize the argon gas which flow atatmospheric pressure. A high AC power supply was used with 1.1kV and 19.57 kHz. Non-thermal Argon plasma used on bloodsamples to show the ability of non-thermal plasma to promote bloodcoagulation. Three tests have been done to show the ability of plasmato coagulate both normal and anti-coagulant blood. Each bloodsample has been treated for varying time from 20sec. to 180sec. atdifferent distances. The results of the current study showed that thecold plasma produced from argon significantly increase the in vitrospeed of blood coagulation, the plasma increases activation andaggregation of platelets, causes proliferation of fibroblasts and fibrinproduction accelerates blood coagulation.